Local strain tuning for scalable quantum photonics - Ovvyan, Anna; Pernice, Wolfram (Nature materials, 2025)
A scalable and reconfigurable hybrid photonic platform integrates multiple wavelength-tunable quantum emitters with a low-loss lithium niobate circuit, achieving on-chip spectral control and quantum interference, a key step towards fully integrated quantum photonic networking and computation on-chip.